2010
DOI: 10.1016/j.bpj.2010.09.034
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Dynamics of Multistage Cell Lineages in Tissue Stratification

Abstract: In developing and self-renewing tissues, terminally differentiated (TD) cell types are typically specified through the actions of multistage cell lineages. Such lineages commonly include a stem cell and multiple progenitor (transit-amplifying) cell stages, which ultimately give rise to TD cells. As the tissue reaches a tightly controlled steady-state size, cells at different lineage stages assume distinct spatial locations within the tissue. Although tissue stratification appears to be genetically specified, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
55
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 51 publications
(56 citation statements)
references
References 38 publications
(46 reference statements)
1
55
0
Order By: Relevance
“…We could determine the number of cells in each compartments at different time of development (from E11.5 to E15.5), but it is not yet technically possible to evaluate the flow of melanoblasts going from the dermis to epidermis. Other mathematical models have already been established to determine the proliferation features for cells in culture or in vivo (Chou et al, 2010;Di Garbo et al, 2010;Hyrien et al, 2010;Tabatabai et al, 2011;Tomasetti and Levy, 2010). However, none of them brings clear values of doubling times of their considered cells, as we do.…”
Section: Establishment Of the Melanocyte Lineagementioning
confidence: 87%
“…We could determine the number of cells in each compartments at different time of development (from E11.5 to E15.5), but it is not yet technically possible to evaluate the flow of melanoblasts going from the dermis to epidermis. Other mathematical models have already been established to determine the proliferation features for cells in culture or in vivo (Chou et al, 2010;Di Garbo et al, 2010;Hyrien et al, 2010;Tabatabai et al, 2011;Tomasetti and Levy, 2010). However, none of them brings clear values of doubling times of their considered cells, as we do.…”
Section: Establishment Of the Melanocyte Lineagementioning
confidence: 87%
“…Such feedback can also drive the spatial stratification of epithelia (Chou et al 2010). Moreover, such studies show that in multistage lineages, the relative strengths of the different feedback loops determine which cell stage adopts stem or committed progenitor cell behaviors and suggest that feedback is the reason why stem and committed progenitor cell behaviors emerge in tissues.…”
Section: Introductionmentioning
confidence: 99%
“…These population dynamic models could include age structure (29), evolution (27,30), and stochasticity (30,31); and these models could also be applied to the regulation of cancer (32). Studies based on spatial modeling have found that diffusive and regulatory molecules involved in feedback mechanisms regulating the differentiation capabilities of the cells are important in maintaining the stem cell niche and shaping tissue stratification (33,34).…”
mentioning
confidence: 99%